2011
DOI: 10.1007/dcr.0b013e31820eee2e
|View full text |Cite
|
Sign up to set email alerts
|

Is the Outcome of Transanal Advancement Flap Repair Affected by the Complexity of High Transsphincteric Fistulas?

Abstract: The complexity of high transsphincteric fistulas does not affect the outcome of transanal advancement flap repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The success rate of fibrin glue was 14-63% [16,17]. The cure rate of Mucosa advancement flap was 66-87% but the recurrence rate was high [18][19][20]. And mild to moderate incontinence occurred in 35% of the patients after operation.…”
Section: Discussionmentioning
confidence: 96%
“…The success rate of fibrin glue was 14-63% [16,17]. The cure rate of Mucosa advancement flap was 66-87% but the recurrence rate was high [18][19][20]. And mild to moderate incontinence occurred in 35% of the patients after operation.…”
Section: Discussionmentioning
confidence: 96%
“…Although advances in surgery and technology have led to various ''minimally invasive'' approaches [1,2], results in terms of success rate and recurrence are quite disappointing. The failure rate is approximately 30-60 % for established surgical procedures such as the endorectal advancement flap (ERAF) [3,4] and injection of biological glues [5,6]. Also the initial enthusiasm for even newer techniques, such as anal fistula plug [7,8] and ligation of the intersphincteric fistula tract (LIFT) [9,10], decreased at the long-term follow-up, with a recurrence rate of about 70-80 % and 30-60 %, respectively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, examining the complexity of high transsphincteric fistulae, we observed associated abscesses in 36% of patients. Abscesses occurred more frequently in patients with an internal opening located posteriorly than anteriorly (47% vs 5%) . In the present study, the incidence of associated abscesses was 54% in patients with a high transsphincteric fistula and 4% in those with a low transsphincteric fistula.…”
Section: Discussionmentioning
confidence: 46%